Delay dependent from the goods of the price in the Kaleckian model - Barzdžiukas, Raimondas; Eitkevičiūtė, Rasa; Švitra, Osvaldas (Lietuvos matematikos rinkinys, 2012)
In this article we investigate models of economical growth, where delay depends on appropriate solutions, i.e., prices of goods.